Risiko Misleading Information Laporan Keuangan Penerbit UMKM pada Securities Crowdfunding: Mengimplementasikan BLU sebagai Auditor untuk menjamin Perlindungan Pemodal - Zaki Priambudi; Bima Rico Pambudi; Natasha Intania Sabila (Jurnal Penelitian Hukum De Jure, 2023)
Securities Crowdfunding (SCF) is expected to be a fast, cheap, and massive alternative funding system for Micro, Small, and Medium Enterprises (MSMEs). However, its implementation is far from ideal. Several studies in China, Britain, and America concluded that SCF is one of the riskiest investment instruments. This is closely related to the lack of implementation of audit obligations on the financial statements of MSMEs as Issuers. To analyze the above problems, this study applied doctrinal research methods and Reform Oriented Research. This study aimed to analyze the urgency of establishing the Public Service Agency of Securities Crowdfunding (BLU SCF) in the implementation of the SCF ecosystem in Indonesia and design the idea of regulating BLU SCF as an SCF auditor. This research found that: (1) the urgency of establishing BLU SCF includes the high default risk by the Issuers, the responsibility exemption from the Issuers and the Organizers for the truth of the financial statements, and there is a potential conflict of interest between the Issuers and the Organizers; (2) BLU SCF will be authorized to audit the reports and other financial documents published by the Issuers through the Organizers. Institutionally, BLU SCF will be under the auspices of the Ministry of Cooperatives and Small and Medium Enterprises. This idea is expected to improve the practice of SCF implementation in Indonesia, by prioritizing the protection of Investors’ rights to the truth of the Issuer’s financial statements.